Pelletalization Techniques: A Review - Vaphare, Ashok M; Banerjee, DR. S K; Gadhave, M V; Gaikwad, DR.D D (Asian Journal of Pharmaceutical Research and Development, 2014)
In present times, the pelletization technologies are giving much attention as they represent an efficient pathway for manufacture of new drug delivery system .It has good advantage over the conventional dosage form. Pelletization technique help in the formation of spherical beads or pellets having a diameter 0.5 -1.5 mm which can be eventually coated for preparation of modified release dosage form .It leads to an improvement in flow ability, appearance and mixing properties thus avoiding for generation of excessive dust and reduces segregation and remove the undesirable properties and improve the physical and chemical properties of fine powder. The aim of this study is to provide detailed and different techniques of pelletization such as powder layering, suspension /solution layering, extrusion and spheronization, cryopelletization, etc. It also gives a brief idea about the evaluation of pellets and application of pelletization technique.